Respuesta :

Answer:

[tex]y=\displaystyle\frac{3}{2}x-3[/tex]

Step-by-step explanation:

Hi there!

Slope-intercept form: [tex]y=mx+b[/tex] where m is the slope and b is the y-intercept (the value of y when x=0)

We're given:

⇒ x-intercept = 2

⇒ y-intercept = -3

1) Determine the slope (m)

[tex]m=\displaystyle\frac{y_2-y_1}{x_2-x_1}[/tex] where two points that fall on the line are [tex](x_1,y_1)[/tex] and [tex](x_2,y_2)[/tex]

Given the x- and y-intercepts, we can rewrite them as points:

x-intercept = 2

⇒ (2,0)

y-intercept = -3

⇒ (0,-3)

Plug these points into the equation:

[tex]m=\displaystyle\frac{0-(-3)}{2-0}\\\\m=\displaystyle\frac{0+3}{2}\\\\m=\displaystyle\frac{3}{2}[/tex]

Therefore, the slope of the line is [tex]\displaystyle\frac{3}{2}[/tex]. Plug this into [tex]y=mx+b[/tex]:

[tex]y=\displaystyle\frac{3}{2}x+b[/tex]

2) Plug in the y-intercept (b)

[tex]y=\displaystyle\frac{3}{2}x+b[/tex]

We're given the y-intercept: -3. Plug this into [tex]y=\displaystyle\frac{3}{2}x+b[/tex]:

[tex]y=\displaystyle\frac{3}{2}x+(-3)\\\\y=\displaystyle\frac{3}{2}x-3[/tex]

I hope this helps!

ACCESS MORE